IMPLEMENTASI MANAJEMEN KURIKULUM SEBAGAI UPAYA PENINGKATAN KUALITAS PENDIDIKAN DI MTS NURUL IMAN TANJUNG MORAWA - Fitri Yanti Nasution (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to describe the implementation of curriculum management in aneffort to improve the quality of education in Mts Nurul Iman Tanjung Morawa. This research was conducted at Mts Nurul Iman Tanjung Morawa by using a descriptive approach. As informants in this study was the principal, vice principal, vice principal areas of the curriculum. Data collection techniques used in this research is with interviews, observation and documentation. Data analysis was performed by means of the reduction of the data, the presentation of data, and the withdrawal of the conclusion. Testing the validity of the data is done by way of credibilitas, transferabilitas, dependabilitas, and confirmabilitas. The findings of this research show that: 1) planning curriculum was drawn up with the curriculum development team consists of the head of sekolag Ment Nurul Iman Tanjung Morawa, vice principal Mts Nurul Iman Tanjung Morawa, Deputy Head of school curriculum parts move made was to analyze the needs and identifying standards needs. 2) implementation of curricula at the school MTs Nurul Iman Tanjung Morawa is done by conducting oversight towards the implementation of the curriculum in school Mts Nurul Iman that is done by the head of school. 3) curriculum Evaluation is carried out by means of checking documents, interviews and curriculum supervision classes. 4) obstacles management school curriculum penimplementasian MTs Nurul Iman Tanjun Morawa is academic responsibilities and still have to be increased again, and the motivation of teachers who teach in the schools of Mts Nurul Iman Tanjung Morawa. Keywords: Management Curriculum, Improving The Quality Of Education